EFFICACY OF INTRAVENOUS IRON SUCROSE IN WOMEN WITH IRON DEFICIENCY ANEMIA IN THIRD TRIMESTER VISITING TO A TERTIARY CARE HOSPITAL (The Research of Medical Science Review, 2025)
OBJECTIVE: To determine the efficacy of intravenous iron sucrose in women with iron deficiency anemia in third trimester visiting to a tertiary care hospital.METHODOLOGY: This cross-sectional research endeavor is scheduled for execution in 2024 within the Obstetrics & Gynecology Department of Liaquat University of Medical and Health Sciences, Jamshoro, and will involve the enrollment of 146 pregnant women diagnosed with iron deficiency anemia (hemoglobin levels <10 g/dL, ferritin levels <10 μg/L) during the third trimester of gestation. Eligible participants have a singleton pregnancy over 20 weeks and are aged 20-35 years and will be given iron sucrose intravenously on alternate days. After four weeks, hemoglobin levels will be reassessed, with a concentration above 11 g/ dL deemed indicative of treatment effectiveness. The dataset will undergo analysis through the application of SPSS version 26, employing both descriptive statistics and the chi-square test for evaluation.RESULTS: The mean age of the participants was 25.9 years (±4.8 SD). Prior to the intervention, the average hemoglobin concentration was recorded at 9.09±0.50 g/dL, whereas the serum ferritin levels exhibited an average of 24.44±9.09 ng/mL. Subsequent to the administration of iron therapy, hemoglobin concentrations demonstrated a statistically significant enhancement (p=0.000), and improvements in serum ferritin levels were also observed (p=0.044). The intervention proved to be particularly effective among women possessing a normal Body Mass Index (81.6%), elevated educational attainment (82.9%), and superior socioeconomic standing (83.7%).CONCLUSION: The research elucidated a significant increase in hemoglobin and serum ferritin concentrations subsequent to the implementation of the intervention, thereby reinforcing the assertion that intravenous iron sucrose constitutes a viable therapeutic strategy for addressing iron deficiency anemia during the perinatal phase. Considering its established effectiveness and safety characteristics, intravenous iron sucrose continues to be regarded as a reliable strategy for enhancing maternal health and promoting positive outcomes for both the mother and the newborn.